Relapse of porphyria cutanea tarda after treatment with phlebotomy or 4‐aminoquinoline antimalarials: a meta‐analysis3. (26th July 2018) - Salameh, H.; Sarairah, H.; Rizwan, M.; Kuo, Y.‐F.; Anderson, K.E.; Singal, A.K.
Summary: Background: Porphyria cutanea tarda (PCT) is the most common human porphyria. It is caused by hepatic deficiency of uroporphyrinogen decarboxylase activity, which is acquired in the presence of multiple susceptibility factors. PCT presents clinically with cutaneous blistering photosensitivity and is readily treatable with either repeated phlebotomy or 4‐aminoquinoline antimalarials. Objectives: To perform a systematic review and meta‐analysis to compare the effectiveness of these quite different treatment approaches, especially on relapse rates (RRs) after achieving remission. Methods: Published studies that included follow‐up for at least 1 year after treatment of PCT were included. The primary study outcome was PCT relapse. Pooled data are reported as the RRs per person‐year of follow‐up with 95% confidence intervals (CIs). Results: Of 375 articles identified as pertaining to PCT treatment, 12 were eligible for analysis. Of these, five used high‐dose 4‐aminoquinoline regimens (two combined with phlebotomy and three without phlebotomy), five used low‐dose 4‐aminoquinoline regimens and three used phlebotomy. RRs during the year after treatment were similar for the high‐ and low‐dose 4‐aminoquinoline groups (35–36%) and lower in the phlebotomy group (20%). The pooled RRs with their 95% CIs were 8·6 (3·9–13·3) per 100 person‐years in the high‐dose 4‐aminoquinoline group, 17·1 (8·9–25·3) per 100 person‐years in the low‐dose 4‐aminoquinoline group and 5·1 (0·5–10·6) per 100 person‐years in the phlebotomy group. Subgroup and sensitivity analyses showed similar results. Conclusions: Clinical or biochemical RRs ranged from 5 to 17 per 100 person‐years after remission of PCT. Relapses were somewhat more frequent after remission with 4‐aminoquinoline regimens than after remission following phlebotomy. Prospective studies are needed to define better how often relapses occur with these treatments after documenting both clinical and biochemical remission of PCT. Abstract : What's already known about this topic? Porphyria cutanea tarda (PCT) is a chronic disease with potential for relapse. What does this study add? The relapse rate of PCT based on this meta‐analysis is about 5–17 per 100 person‐years of follow‐up after achieving remission. The relapse rate is somewhat higher after remission with 4‐aminoquinolines, especially using a low‐dose regimen, compared with remission after phlebotomy. Respond to this article Plain language summary available online